PERSPECTIVES, NORMS, AND AGENCY. Issue 1 (14th June 2017) - Muldoon, Ryan
Abstract: A core set of assumptions in economic modeling is that rational agents, who have a defined preference set, assess their options and determine which best satisfies their preferences. The rational actor model supposes that the world provides us with a menu of options, and we simply choose what's best for us. Agents are independent of one another, and they can rationally assess which of their options they wish to pursue. This gives special authority to the choices that people make, since they are understood to be the outcomes of the agent's considered judgments. However, we have come to see that the independence assumption does not always hold in the way that we may have initially thought. Social norms can govern our choices even when we disagree with them. Here we can begin to see how the standard model of choice and agency begins to weaken: no longer are my choices wholly mine, but instead there is a subset of choices that are governed by the broader culture that I live in. Social norms constrain my behavior with informal coercion — my desire to remain a community member in good standing requires me to behave in accordance with the community's social norms. What I wish to challenge more substantively is the claim that the menu of choices agents "see" is in fact the objective set of options that is transparently provided by the world. Instead, I argue that the options that people perceive and the evidence they use to make choices are mediated by perspectives. Perspectives can importantly interact with social norms to make some norms more resilient to change, and others harder to adopt. This further shapes both our descriptive and normative understanding of agency. Our choices are not over all of the objectively available options, but over the options that we can see. The evidence we marshal to support our choices is not the full set of evidence, but the evidence that we recognize as salient. This is not to deny that individuals have agency, but rather we need a more nuanced understanding of the nature of this agency.